HUBUNGAN SELF-EFFICACY DAN PROKRASTINASI AKADEMIK MAHASISWA DALAM MENYELESAIKAN TUGAS PERKULIAHAN - Damri Damri; Engkizar Engkizar; Fuady Anwar (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2017)
The research is aimed at knowing the self-efficacy catogories and students academic procrastination and finding out the correlation of the two variables toward students’ their academic assignment accomplishment. Quantitative method is used in the research. Data was obtained through 231 respondents using self-efficacy and academic procrastination instruments. The data then is analyzed by SPSS for windows release 20.0. The findings show that students’ self-efficacy belongs to high category (71,90%) while procrastination is in moderate category (52,30%). Analysis of Pearson Product Moment Correlation shows that there is negative correlation between self-efficacy and academic procrastination (rcount)=-0.590 out of 0,000 significance level. It is implied that the more self-efficacy possessed by a students, the lower is the academic procrastination. Otherwise, the lower self-efficacy possessed by a students, th higher is the academic procrastination.